Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1103/physrevlett.113.091104
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the Equation of State of Neutron Stars from Binary Mergers

Abstract: Determining the equation of state of matter at nuclear density and hence the structure of neutron stars has been a riddle for decades. We show how the imminent detection of gravitational waves from merging neutron star binaries can be used to solve this riddle. Using a large number of accurate numerical-relativity simulations of binaries with nuclear equations of state, we find that the postmerger emission is characterized by two distinct and robust spectral features. While the high-frequency peak has already … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
378
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(411 citation statements)
references
References 38 publications
26
378
7
Order By: Relevance
“…Furthermore, this method could be adapted to constrain or search for other smallamplitude features that might be shared by a population of events, e.g. common parameterized post-Einsteinianlike [43] corrections to the inspiral phase of the mergers, or common equation-of-state-discriminating frequencies excited in hypermassive remnants of binary neutron star mergers [44][45][46][47][48][49][50][51][52][53][54]. In this latter example, one issue in adapting the coherent stacking method would be achieving phase alignment, due to the challenge in accurately calculating the details of the matter dynamics post-merger.…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…Furthermore, this method could be adapted to constrain or search for other smallamplitude features that might be shared by a population of events, e.g. common parameterized post-Einsteinianlike [43] corrections to the inspiral phase of the mergers, or common equation-of-state-discriminating frequencies excited in hypermassive remnants of binary neutron star mergers [44][45][46][47][48][49][50][51][52][53][54]. In this latter example, one issue in adapting the coherent stacking method would be achieving phase alignment, due to the challenge in accurately calculating the details of the matter dynamics post-merger.…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…Besides the prominent peak at f peak , there are several additional peaks in the spectra (see Fig.5). It is suggested that these minor peaks contains rich information of the NS structure [33,[67][68][69].…”
Section: Extraction Of Radius Information By Gw From Merger Remnant Nsmentioning
confidence: 99%
“…(1), which depends on the peak frequency f peak , the quality factor Q, the 22 mode amplitude A 0 , the angle-dependent amplitude factor A r and phase offset ϕ 0 . We estimate the 22 mode frequency (f peak ) using the fit of [12] (see also [11,14,[58][59][60][61] for other fits)…”
Section: B MC Studymentioning
confidence: 99%
“…More than a decade of simulations of BNS mergers have revealed that the postmerger GW spectrum is rich, with several distinct peaks that can be used to probe the merger remnant through spectroscopy (see e.g. [5][6][7][8][9][10][11][12][13][14][15][16][17] for some historical and recent work, [18][19][20][21] for related work on BH spectroscopy, and [22,23] for recent reviews). In the first 10-20 ms after merger, the dominant component of a postmerger GW is the l ¼ m ¼ 2 mode (which we call here the 22 mode for short).…”
Section: Introductionmentioning
confidence: 99%